3D printed super-anti-freezing self-adhesive human-machine interface. (July 2021) - Chen, Lei; Wang, Zhaolong; Zhan, Ziheng; Xie, Mingzhu; Duan, Guihui; Cheng, Ping; Chen, Yiqin; Duan, Huigao
Abstract: A 3D printed adhesive and conductive hydrogel with super-anti-freezing property is reported. This hydrogel exhibits excellent stretchability (elongation up to 3920%), outstanding adhesive behavior (adhesion strength up to 61 kPa), as well as marvelous anti-freezing ability (glass transition temperature as low as −96.3 °C). The present 3D printed hydrogel can be used as a sensor with a broad strain range to monitor human motions, slight physiological changes even at an extremely low temperature of −80 °C. Moreover, the hydrogel based self-adhesive electrodes can adhere to human skin directly to collect electrocardiogram, electro-oculogram and electromyogram signals accurately, promising the hydrogel electrodes to serve as a human-machine interface for controlling synchronized motion of anthropomorphic robots, exemplified by playing the piano. We also show that fingers of extraman can be precisely controlled via the self-adhesive hydrogel electrodes even at extremely low temperature of −80 °C. Therefore, the hydrogel fabricated by 3D printing is supposed to have promising potential applications in wearable devices, human-machine interactions, and intelligent bio-electronics, especially under harsh environmental conditions such as extreme low temperature. Graphical abstract: Image 1 Highlights: The hydrogel is fabricated by Projection Micro-StereoLithography 3D printing technique. The hydrogel shows high stretchable, adhesive, and super-anti-freezing characteristic. Micro-structured hydrogel sensor can monitor human motion with high sensitivity. The hydrogel can collect electrophysiological signals for controlling motion of robots, even at extremely low temperature.